Peribiliary Glands as a Niche of Extrapancreatic Precursors Yielding Insulin‐Producing Cells in Experimental and Human Diabetes. (26th February 2016) - Carpino, Guido; Puca, Rosa; Cardinale, Vincenzo; Renzi, Anastasia; Scafetta, Gaia; Nevi, Lorenzo; Rossi, Massimo; Berloco, Pasquale B.; Ginanni Corradini, Stefano; Reid, Lola M.; Maroder, Marella; Gaudio, Eugenio; et al.
Abstract: Peribiliary glands (PBGs) are niches in the biliary tree and containing heterogeneous endodermal stem/progenitors cells that can differentiate, in vitro and in vivo, toward pancreatic islets. The aim of this study was to evaluate, in experimental and human diabetes, proliferation of cells in PBGs and differentiation of the biliary tree stem/progenitor cells (BTSCs) toward insulin‐producing cells. Diabetes was generated in mice by intraperitoneal injection of a single dose of 200 mg/kg ( N = 12) or 120 mg/kg ( N = 12) of streptozotocin. Liver, pancreas, and extrahepatic biliary trees were en bloc dissected and examined. Cells in PBGs proliferated in experimental diabetes, and their proliferation was greatest in the PBGs of the hepatopancreatic ampulla, and inversely correlated with the pancreatic islet area. In rodents, the cell proliferation in PBGs was characterized by the expansion of Sox9‐positive stem/progenitor cells that gave rise to insulin‐producing cells. Insulin‐producing cells were located mostly in PBGs in the portion of the biliary tree closest to the duodenum, and their appearance was associated with upregulation of MafA and Gli1 gene expression. In patients with type 2 diabetes, PBGs at the level of the hepatopancreatic ampulla contained cells showing signs of proliferation and pancreatic fate commitment. In vitro, high glucose concentrations induced the differentiation of human BTSCs cultures toward pancreatic beta cell fates. The cells in PBGs respond to diabetes with proliferation and differentiation towards insulin‐producing cells indicating that PBG niches may rescue pancreatic islet impairment in diabetes. These findings offer important implications for the pathophysiology and complications of this disease. Stem Cells 2016;34:1332–1342 Abstract : Peribiliary glands (PBGs) are located throughout the extrahepatic biliary tree and represent the niche of multipotent (Sox9+) biliary tree stem/progenitor cells (BTSC). In our experimental models, streptozotocin (STZ) administration determined the reduction of pancreatic islets and a correlated increase of PBG mass; in STZ models, PBGs are characterized by the expansion of Sox9 + proliferating cells, the increase of mucinous cells, and the appearance of insulin‐producing cells. In parallel, at the level of hepatopancreatic ampulla, Type 2 Diabetic (T2D) patients showed PBG hyperplasia, proliferation, and signs of endocrine pancreatic commitment in comparison with normal subjects. In summary, our findings indicated that cells in PBGs respond to diabetes with proliferation and differentiation towards insulin‐producing cells.